The first post-cardiac injury syndrome reported following transcatheter aortic valve implantation: a case report. Issue 4 (28th September 2018) - Llubani, Redi; Böhm, Michael; Imazio, Massimo; Fries, Peter; Khreish, Fadi; Kindermann, Ingrid
Abstract: Background: Post-cardiac injury syndrome is a form of secondary pericarditis with or without pericardial effusion, which typically occurs weeks to months following an injury to the heart or pericardium. Disease activity can be followed with serial testing of inflammatory markers e.g. C-reactive protein (CRP) and/or sedimentation rate, electrocardiogram, and echocardiography. Case summary: A 79-year-old woman was admitted with chest pain, dyspnoea at rest, cough, and low degree fever. The patient had undergone transcatheter aortic valve implantation (TAVI) 6 months before admission. Inflammatory markers were increased and a chest X-ray and computed tomography (CT) showed a minimal left pleural effusion. An empirical antibiotic treatment and ibuprofen to control chest pain were started on the presumption of an acute bronchitis. Despite 15 days of different antibiotic protocols the markers of inflammation remained increased. A positron emission tomography with computed tomography and cardiac magnetic resonance imaging showed signs of an aseptic pericarditis. After having excluded any infectious, metabolic, drug-induced or neoplastic genesis we considered the diagnosis of late onset autoimmune-mediated pericarditis. Subsequently, treatment was promptly initiated with colchicine and prednisone. The patient reported clinical improvement in the following days and the CRP value continuously decreased. Discussion: To the best of our knowledge, this is the first reported case of post-cardiac injury syndrome after TAVI. It should be considered in those patients who have persistent chest pain, fever, fatigue, and elevated inflammatory markers after a TAVI procedure, even though it may occur weeks or months after the intervention. A triple therapy with colchicine, ibuprofen, and low-dosage steroids may be used for persistent symptoms.